Effectiveness of Deep Brain Stimulation in Iraqi Patients with Parkinson Disease - Bassam Mahmood Flamerz Arkawazi1 , Anwer Noori Hafdh2 , Zaki Noah Hasan3 , Awfa Aktham Abdullateef4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Surgical treatment for advanced Parkinson disease (PD) is considered when medical therapyfails to control the symptoms.Objective: Assessment of effectiveness of deep brain stimulation (DBS) in controlling motor manifestationsof advanced PD.Patients and Method: Twenty patients (14 male and 6 female) whom fulfill the requirements for DBSsurgery, were included in this study. All patients were on Levodopa (L-dopa), procyclidine, pramipexol, andamantadine medications. The study conducted between March 2017 and March 2018 in the neurosurgicalteaching hospital and neuroscience hospitalin Baghdad/Iraq. Unified Parkinson’s Disease RatingScale(UPDRS) was used before and after surgery.Results: There was a statistically significant improvement in the tremor, rigidity, and bradykinesia.Conclusion: Most disabling axial symptoms of gait and postural instability, that failed to respond to medicaltherapy, will show effective response to the bilateral STN stimulation in advanced PD cases.